Substantial increase in perceived benefits over harms of COVID-19 outbreak but persistent socioeconomic disparities: Comparison of two cross-sectional surveys in Hong Kong from 2020 to 2021 - Leung, Hiu Tin; Gong, Wei Jie; Sit, Shirley Man Man; Lai, Agnes Yuen Kwan; Ho, Sai Yin; Wang, Man Ping; Lam, Tai Hing (Frontiers in Public Health, 2022)
Background: We have reported both perceived benefits and harms of the COVID-19 outbreak and their socioeconomic disparities amid the pandemic in Hong Kong. We further investigated whether such perceptions and disparities had changed after 10 months. Methods: Under the Hong Kong Jockey Club SMART Family-Link Project, we conducted two cross-sectional surveys online on perceived personal and family benefits and harms of the COVID-19 outbreak in Hong Kong adults in May 2020 (after Wave 2 was under control; N = 4891) and in February and March 2021 (after Wave 4 was under control; N = 6013). We collected sociodemographic information, including sex, age, education, household income, and housing. Using multivariate models of analysis of covariance (MANCOVA), we compared perceived benefits and harms and socioeconomic disparities between the two surveys. Results: Adjusting for sex and age, the prevalence of 17 out of 18 perceived personal and family benefits of COVID-19 outbreak increased (Ps < 0.001). Six of 11 perceived personal and family harms decreased (Ps < 0.001) and 4 increased (Ps < 0.001). The total number of perceived personal and family benefits increased substantially (Ps < 0.001), whereas that of perceived personal harms decreased (P = 0.01) and family harms remained stable (P > 0.05). Socioeconomic disparities, however, persisted — more perceived benefits in those with higher socioeconomic status (Ps < 0.001) and more perceived harms in those with lower (Ps ≤ 0.005). Conclusion: We have first reported that perceived personal and family benefits of the COVID-19 outbreak increased substantially over 10 months amid the pandemic, while perceived personal and family harms were lower and stable, respectively. Socioeconomic disparities of the perceived benefits and harms persisted, which need to be monitored and addressed urgently.